Analysis of Cardiorespiratory Endurance Levels of High School Futsal Teams - Zainuddin, M. Said; Riyadi, Slamet; Zakaria, Ahmad (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to find out how good the cardiorespiratory endurance level of the SMA Negeri 22 Makassar futsal team is. This research is a quantitative descriptive research, the test technique used to collect data is the Multistage Fitness Test. The population in this study was 25 futsal team players at SMA Negeri 22 Makassar, the sample to determine the population used purposive sampling. The data analysis technique used is descriptive statistics in the form of percentages. The prevalence of